Optimizing the Islamic Religious Education Learning Model at Elementary School: Challenges and Innovations - Kamaruddin Kamaruddin; Akhsanul In’am; Abbul Haris; M Nurul Humaidi (STAI Hubbulwathan Duri, 2025)
Islamic Religious Education (PAI) in remote Indonesian elementary schools is critical for character development but faces challenges such as limited resources, inadequate infrastructure, and low community literacy. This study examines the implementation, challenges, and effectiveness of the PAI learning model at SD Negeri 010 Kampung Terpencil, Natuna Regency—a remote island school with unique geographical and social constraints. Using a qualitative, interpretive paradigm with a phenomenological and descriptive approach, data were collected through in-depth interviews, classroom observations, and document analysis. Subjects included school administrators and PAI teachers. Data were analyzed through concrete description, pattern identification, data reduction, and interpretation. Findings reveal a predominance of teacher-centered approaches, though student-centered methods are applied selectively in practical lessons like prayer and ablution. Constraints such as small student numbers, limited infrastructure, and lack of teacher training hinder interactive learning. However, innovative strategies—including outdoor learning, technology use, and collaboration with external educators—have improved student engagement. Still, disparities in learning outcomes persist. Despite contextual innovations, the overall effectiveness of PAI learning remains moderate due to structural limitations. Sociocultural and contextual learning theories support the applied strategies, yet further support is needed to optimize outcomes. Recommendations include infrastructure enhancement, teacher development, and adaptive pedagogical approaches tailored to remote settings.